2004
DOI: 10.1016/j.femsec.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of polycyclic aromatic hydrocarbons (PAHs) by Cladosporium sphaerospermum isolated from an aged PAH contaminated soil

Abstract: The ability of a Deuteromycete fungus, Cladosporium sphaerospermum, previously isolated from soil of an aged gas manufacturing plant, to degrade polycyclic aromatic hydrocarbons was investigated. This strain was able to degrade PAHs in non-sterile soils (average 23%), including high molecular weight PAHs, after 4 weeks of incubation. In a microcosm experiment, PAH depletion was clearly correlated to fungal establishment. In liquid culture, this strain degraded rapidly benzo(a)pyrene during its early exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 39 publications
0
64
2
1
Order By: Relevance
“…The degradation values obtained by the marine-derived fungi were considered satisfactory in comparison with others studies regarding PAH degradation by non-ligninolytic fungi belonging to the ascomycota and zygomycota phyla. [18][19][20] In Figure 5, the chromatograms referring to the fermentative media containing the fungi that presented the lowest (Penicillium sp. CBMAI 851) and the highest (Aspergillus sclerotiorum CBMAI 849) results for the degradation of pyrene and benzo[a]pyrene are presented.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation values obtained by the marine-derived fungi were considered satisfactory in comparison with others studies regarding PAH degradation by non-ligninolytic fungi belonging to the ascomycota and zygomycota phyla. [18][19][20] In Figure 5, the chromatograms referring to the fermentative media containing the fungi that presented the lowest (Penicillium sp. CBMAI 851) and the highest (Aspergillus sclerotiorum CBMAI 849) results for the degradation of pyrene and benzo[a]pyrene are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Wood and other lignocellulosic materials are formed from three main polymeric constituents: cellulose, lignin, and hemicelluloses [9]. It was reported that many wood rotting fungus plays an important role in the biodegradation of polycyclic hydrocarbons (PAHs) [10]. There are reports that oxalic acid produced by fungi presumably precipitates copper into insoluble form of the oxalate, rendering the copper metabolite inert.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Bioaugmentation with Cladosporium sphaerospermum significantly stimulated PAH degradation, especially for high molecular weight PAH [66]. Other authors have reported a significantly improved degradation of high molecular weight PAH after bioaugmentation in PAH-contaminated soil [24,29].…”
Section: Phenanthrene Removal By a Niger Mnp +7 And Wild-type Strainmentioning
confidence: 91%